2013
DOI: 10.1542/peds.2012-0788
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prepregnancy BMI and Child Cognition: A Longitudinal Cohort Study

Abstract: Maternal prepregnancy BMI is negatively associated with children's cognitive performance, even after adjusting for multiple socio-demographic confounders and children's BMI. The relationship appears to become stronger as children get older, although the overall effect size is modest. In utero fetal programming or residual confounding may explain these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 28 publications
4
98
1
1
Order By: Relevance
“…To date, there have been only a few studies to show the independent associations of maternal prepregnancy obesity and offspring's cognitive development. [43][44][45] Hence, studies in the present review that perceived a negative association between maternal diabetes during pregnancy and offspring's cognitive development could have been confounded by maternal prepregnancy obesity.…”
Section: Discussionmentioning
confidence: 90%
“…To date, there have been only a few studies to show the independent associations of maternal prepregnancy obesity and offspring's cognitive development. [43][44][45] Hence, studies in the present review that perceived a negative association between maternal diabetes during pregnancy and offspring's cognitive development could have been confounded by maternal prepregnancy obesity.…”
Section: Discussionmentioning
confidence: 90%
“…Associations have been reported between prepregnancy obesity and intellectual disability, 12,16 lower cognitive performance, 10,13,14,17,21 ADHD, 11,19,20,32 and autism 15 in children. One null study was also reported; however, it was limited by assessing all overweight and obese women as a single group.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Recent epidemiologic studies suggest associations between prepregnancy obesity and various neurodevelopmental outcomes. [10][11][12][13][14][15][16][17][18][19][20][21] However, these studies were limited by small sample sizes, insufficient information on confounders and mediators, and imprecise neurodevelopment measures. Additionally, 1 study reported no association.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and human studies have shown that maternal obesity during pregnancy predisposes the offspring to develop metabolic disorders [16][17][18] and increases the risk of cognitive decline later in life [19], associated with alterations in brain development, hypothalamic organisation and metabolism in the adult offspring [20,21]. A reduction in cognitive development and performance was recently reported at early life stages or in pre-school/school children born to obese mothers [22,23]. Nevertheless, in vivo brain glucose metabolism, in the context of fetal programming and maternal obesity, has not been specifically investigated.…”
Section: Introductionmentioning
confidence: 99%